2014
DOI: 10.1097/opx.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Scaling for the Estimation of Aberrations in Natural Pupils

Abstract: Estimation of ocular wavefront aberration coefficients either scaling down from large to smaller pupils or scaling up from smaller to large pupils provides estimates that are not significantly different from clinically measured values. However, when scaling up to a larger pupil size, the estimates are more variable. These findings have implications for pupil scaling on an individual basis, such as in cases of refractive surgery or when using pupil scaling to examine a clinical cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The formulas of Diaz et al (2009) and Janssen et al (2006) are equally valid; we use Dai (2006) because it is a relatively simple expression and it appears to be the fastest to compute in our environment. We note that this formula can be used to scale for smaller or larger pupils (ratios less than or greater than 1), though the error is larger for ratios greater than 1 (Bará, Pailos, Arines, López-Gil, & Thibos, 2014;Dai, 2011;Ommani, Hutchings, Thapa, & Lakshminarayanan, 2014). We provide the function ZernikeScalePupil to scale coefficients for smaller or larger pupils.…”
Section: Scaling Zernike Coefficients To a Different Pupil Sizementioning
confidence: 99%
“…The formulas of Diaz et al (2009) and Janssen et al (2006) are equally valid; we use Dai (2006) because it is a relatively simple expression and it appears to be the fastest to compute in our environment. We note that this formula can be used to scale for smaller or larger pupils (ratios less than or greater than 1), though the error is larger for ratios greater than 1 (Bará, Pailos, Arines, López-Gil, & Thibos, 2014;Dai, 2011;Ommani, Hutchings, Thapa, & Lakshminarayanan, 2014). We provide the function ZernikeScalePupil to scale coefficients for smaller or larger pupils.…”
Section: Scaling Zernike Coefficients To a Different Pupil Sizementioning
confidence: 99%
“…But how is difference between these estimated values and the truly measured values? A recent study [ 30 ] showed that the estimation of ocular aberration coefficients by either scaling down from large to smaller pupils or by scaling up from smaller to large pupils provided comparable results from clinically measured values. Although it might be difficult to directly compare the results produced by different instruments (the previous study used a Harmann-shack-principle-based aberrometer, whereas the current study used a ray-tracing-technique-based aberrometer), the comparison we found were more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Another point worth noting is that when using the scaling technique, the rescaled magnitude should be minimal, as the present study applied the largest integer pupil size of all measurements. This is because the results from previous studies suggested that a larger scaling range tended to produce greater variability between measurements [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limits of agreement for the wavefront measurement of the spherical error were found to be between ±0.2 (for a pupil diameter of 4.0 and 6.7 mm) [ 10 ] and ±0.55 D [ 11 ] (for pupil diameters of 4.0 and 6.0 mm) and did not differ between several measurements, also without the use of an cycloplegic agent to block accommodation [ 11 ]. Additionally, e.g., to consider different lighting conditions [ 12 ], wavefront sensors allow to compute the refractive errors for different pupil sizes and/or allow the consideration of different higher order aberrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%